Benjamin B. French family papers - French, Benjamin B. (Benjamin Brown), 1800-1870.; French, Francis O. (Francis Ormond), 1837-1893.; Richardson, William Merchant, 1774-1838.; Tuck, Amos, 1810-1879.
Part I contains correspondence primarily between Benjamin B. French and his half brother Henry Flagg French of Exeter, N.H., journals (1828-1870), poems, clippings, and printed material. Includes Benjamin B. French's observations on New Hampshire politics, freemasonry, his involvement with the Magnetic Telegraph Company, the presidency of Franklin Pierce, social life in Washington, D.C., French's association with Abraham Lincoln, Lincoln's assassination, the Civil War, the years following the Civil War, and Congress.
Part II consists chiefly of the papers of Benjamin B. French, his son Francis Ormond French, and Amos Tuck. Benjamin B. French's correspondence continues topics found in Part I. Francis Ormond French's journals cover his early years in Washington, D.C., as well as his years at the Rittenhouse Academy, Washington, D.C., Phillips Exeter Academy, Exeter, N.H., and Harvard College, Cambridge, Mass. His correspondence provides insight into the life of a prosperous American family of the late nineteenth century in New York, N.Y. Amos Tuck's correspondence pertains to politics, his travels in the Midwest in 1851, and the devastation of the South from the Civil War. Also includes letters of William Merchant Richardson. Francis's correspondents include Harris C. Fahnestock, Daniel Chester French, Lot M. Morrill, Hugh McCulloch, William A. Richardson, and John Sherman.
Microfilm edition of journal, volumes 1-11, available
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts.
Library of Congress Prints and Photographs Division.
Clerk of the U.S. House of Representatives, New Hampshire politician, and commissioner of public buildings in Washington, D.C. Other individuals represented include Benjamin's son Francis Ormond French, financier; Amos Tuck, U.S. representative from N.H., whose daughter Ellen married Francis O. French in 1861; and William Merchant Richardson, chief justice of the New Hampshire Superior Court and father of Benjamin B. French's first wife.
Keywords: Fahnestock, Harris C. -- 1835-1914 -- Correspondence; French, Daniel Chester, -- 1850-1931 -- Correspondence; French, Henry F. -- 1813-1885 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Assassination; McCulloch, Hugh, -- 1808-1895 -- Correspondence; Morrill, Lot M. -- 1812-1883 -- Correspondence; Pierce, Franklin, -- 1804-1869.; Richardson, William A. -- 1821-1896 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; French family; United States. -- Congress; Harvard College (1780- ); Magnetic Telegraph Company; Phillips Exeter Academy; Rittenhouse Academy; Freemasonry; Private schools -- New Hampshire -- Exeter; Private schools -- Washington (D.C.); Reconstruction (U.S. history, 1865-1877); Universities and colleges -- Massachusetts -- Cambridge; Confederate States of America -- History; Middle West -- Description and travel; New Hampshire -- Politics and government; New York (N.Y.) -- Social life and customs; Southern States -- History -- 1865-1877.; United States -- History -- Civil War, 1861-1865.; United States -- History -- 1865-1898.; United States -- Politics and government -- 19th century; Washington (D.C.) -- Social life and customs; Clerks, U.S. House of Representatives; Politicians; Public officials